Philosophy Of Justice In Post-Modern Labor Law: What And How? - Solapari, Nuryati; Amin, Fakhry; Alamsyah, Syahrul (Faculty of Law, Universitas Jenderal Soedirman, 2023)
The main objective of this research is to examine the concept of justice in labor law which has developed in the context of the post-modern era as marked by rapid social and technological changes and a more inclusive view of justice. By using normative research, researchers will conduct an in-depth analysis of relevant literature on the philosophy of justice, labor law, and postmodernism as part of primary and secondary legal materials. The data collection process will involve a thorough literature review, analysis of legal texts, and examination of related documents and articles from reliable sources. The differentiation of this study from other studies is its comprehensive analytical approach to understanding justice in labor law and its focus on changes and adaptations that occur in the post-modern era. these findings will explain the concept of justice in the workplace that has adapted to the challenges of the times. In addition, this study aims to identify obstacles and opportunities in building a fair, diverse and efficient employment system for all stakeholders. By paying attention to social dynamics, technology, and postmodern values, researchers hope that labor law can be more responsive and flexible in maintaining a sense of justice and the balance of power between employers and workers.